Analyzing Consumption Patterns of Low-Income Households Receiving Direct Cash Assistance from Village Funds (BLT-DD): Evidence from Labuan Lelea Village, Donggala District - Ma’rifah, Nur Ainun; Yunus, Santi; Jokolelono, Eko; Yunus, Rita; Rahman, Failur (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
Despite receiving Direct Cash Assistance from Village Funds (BLT-DD), low-income households in Labuan Lelea Village, Donggala Regency, continue to struggle with meeting their basic living needs. They have a limited understanding of how the assistance is divided between expenses for food and other necessities. This research aims to analyze the Consumption Patterns of Low-Income Households Receiving Direct Cash Assistance from Village Funds in Labuan Lelea Village, Donggala Regency using Poverty Gap Index Analysis. The research employs descriptive methods with quantitative and qualitative approaches. This study uses the poverty gap index (Poverty Gap Index-P1) analysis method. The research sample consists of 30 respondents receiving BLT-DD (Direct Cash Assistance from Village Funds) who are outside the Integrated Social Welfare Data (DTKS) or are unregistered. Data collection methods used in this research include literature study through written document collection, particularly documents, articles, scientific works, books, survey methods, and interview methods. The research results show that the expenditure pattern of 30 households receiving BLT Village Fund assistance is used more for food at 70.20 percent while non-food items only account for 29.80 percent. This indicates that BLT assistance funds are primarily used to fulfill basic needs in the form of food, which is characteristic of low-income households where most income or assistance received is focused on meeting daily basic needs, especially food consumption. This research suggests strengthening productive economic programs such as skills training and business capital assistance. Regular evaluation is also needed to ensure proper targeting and program effectiveness in reducing poverty.